DISSOLUTION ENHANCEMENT OF MEFENAMIC ACID BY USING POLYMERIC COMPOSITE MATERIAL IN THE FORM OF SOLID DISPERSED SYSTEMS - YAREMENKO, VOLODYMYR; GOY, ANDRIY (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article comprehensively analyzed the obtained polymer composite materials with mefenminic acid in the form of solid dispersion systems (SDS). Pharmaceutically acceptable and widespread polymers were used as polymer carriers: polyvinylpyrrolidone (PVP) and hydroxypropylmethylcellulose (HPMC). Conventional methods such as the spray drying method and the co-milling method were used to obtain SDS. Along with the aforementioned methods, promising and, at the same time, widely accepted for the pharmaceutical industry methods of wet granulation, such as fluid bed granulation and high shear granulation, were tested. It has been established that wet granulation methods make it possible to obtain SDS with mefenamic acid and significantly improve their dissolution. SDS MA and HPMC produced by the high-shear granulation method and the fluid bed granulation method demonstrate an increase in dissolution by 8,60 and 9,46 times, respectively. At the same time, SDS with PVP obtained by the same methods practically do not show an increase in the dissolution of mefenamic acid. It was also established that SDS MA and HPMC obtained by the methods of spray drying and co-milling demonstrate a significant increase in the dissolution of the active substance compared to SDS, the composition of which includes PVP as a polymer carrier. The most promising from the point of view of increasing the dissolution of the active substance of SDS MA: Mannitol : HMPC (5 : 10 : 85) manufactured by high shear granulation method and by fluid bed granulation method were analyzed for pharmacotechnological parameters (bulk density, fractional composition, flowability, angle of repose, loss on drying, morphological characteristics of particles). Complex empirical indicators are calculated: Carr index: (6,00 – 6,97 excellent fluidity) and Hausner ratio: (1,064 – 1,075 excellent turnover), while MA has a Carr index: (31,82 very poor fluidity) and Hausner ratio: (1,47 very poor fluidity). The results of the analysis of all the investigated parameters characterize the obtained composite materials as meeting the requirements for the production of finished dosage forms. The prospects of obtaining such SDS in terms of enhancing the dissolution of the active substance and the possibility of achieving the target pharmaceutical and technological profile in accordance with the selected dosage form were also confirmed.